International law of relevance to plant genetic resources: A practical review for scientists and other professionals working with plant genetic resources - Bragdon, S.; International Plant Genetic Resources Institute (2004)
While controversies over the ownership, control and exchange of plant genetic resources for food and agriculture (PGRFA) are old, modern-day management of these resources is more complicated than ever before. Developments in international and national law and policy over the past 15 years have changed the working environment for those in charge of managing and making decisions about genetic resources. Today genetic resource managers need to understand the legal and policy environment in order to do their jobs effectively. Those who participate in policy-making face an equally bewildering environment. Trade relations, intellectual property rights, biosafety, indigenous communities and public–private sector relations are just a few of the topics that are always on the table. In addition, everyone faces the prospect of dealing with numerous laws, regulations, guidelines and policies and following events in multiple fora, from those at the national level to the international level. Different political and scientific interests compete for what they want or think is right. And yet, at the end of the day it is clear that nations and people are interdependent for plant genetic resources. This simple fact dictates that we cooperate to ensure the conservation of PGRFA and its orderly management, including the facilitation of access and fair benefit sharing. The task of understanding all the issues of relevance to the conservation and management of plant genetic resources is extremely complex. Derived from the substantive chapters of a comprehensive training manual, this Issues Paper attempts to guide the reader through the international agreements and policies of most relevance to the conservation and management of PGRFA, focusing on how they can be understood, implemented and shaped. In addition, there is a chapter discussing cross-cutting issues. This Issues Paper also contains annexes for the reader wishing to have a better understanding of the economic issues that are integral to the international policy and law-making environment.